DEVELOPMENT OF PHYSICAL FITNESS OF YOUNG TAEKWONDO AT THE STAGE OF INITIAL TRAINING - Nozima Xolmuxammedova (The Conference Hub, 2025)
This article considers the need to analyze the existing methods and pedagogical conditions for achieving the required level of readiness for the development of physical qualities at the stage of physical training in the initial preparatory group, as well as methods for their assessment.
Keywords: taekwondo, physical training, competition, training-exercise, preparation, assessment